E3 ubiquitin ligases Cbl‐b and c‐Cbl downregulate PD‐L1 in EGFR wild‐type non‐small cell lung cancer. Issue 4 (4th February 2018) - Wang, Shuo; Xu, Ling; Che, Xiaofang; Li, Ce; Xu, Lu; Hou, Kezuo; Fan, Yibo; Wen, Ti; Qu, Xiujuan; Liu, Yunpeng
Abstract : Anti‐PD‐1/PD‐L1 therapies have demonstrated prominent clinical effects in the treatment of non‐small cell lung cancer (NSCLC). However, limited understanding of the regulatory mechanisms of PD‐L1 has become one of the biggest challenges for further improving efficacy. In this study, we observed that in wild‐type EFGR cell lines A549 and H460, the ubiquitin ligases Cbl‐b and c‐Cbl inhibit PD‐L1 by inactivating STAT, AKT, and ERK signaling. MiR‐181a and miR‐940 were screened and validated to target Cbl‐b and c‐Cbl, respectively. Furthermore, in NSCLC tissues, the expression of Cbl‐b/c‐Cbl is negatively correlated with PD‐L1 expression. Taken together, these findings indicated a new regulatory mechanism for PD‐L1 in wild‐type EGFR NSCLC cell lines by Cbl‐b and c‐Cbl. Abstract :